Mechanical Properties and Microscopic Geological Features under Uniaxial Compression in Tight Reservoir - Dazhong Ren; Fu Yang; Zhonghui Duan; Tao Tian; Ran Zhou; Dengke Liu (Geofluids)
In this study, to investigate the mechanical properties and microscopic geological features, a series of uniaxial compression, petrophysical properties, X-ray diffraction, elements, and conductivity tests were conducted. The results indicate that quartz and plagioclase are essential minerals determining Upper Triassic sandstone compositions, while quartz plays a dominant role in the Lower Permian sandstones. Due to microcracks, the relationships between porosity and permeability of Upper Triassic sandstones are better than those of Lower Permian sandstones. Observations have shown that silicon and aluminum are the main elements of those rocks. The rocks which have large porosity and permeability have a strong capacity of anticompression resistance. There are good consistencies between the mechanical behavior and the high proportion of rigid minerals. Similarly, the rocks which have abundant silicon and aluminum could better support the structural integrity of rocks. High pore structure heterogeneity and abundant clay minerals have positive influence on the mechanical resistance. Shales have distinct plastic deformation features when compared with the sandstones.